Molding the plastic soul of youth. The Ratio Studiorum and the manifacture of educated and catholic subjects - Dallabrida, Norberto (Rivista di Storia dell’Educazione, 2021)
This essay intends to re-read the Ratio Studiorum by analyzing its strategies and pedagogical tactics in the production of the subjectivity of Jesuitic students, in connection with the ascetic principles of the Society of Jesus and the social circumstances of a century characterized by religious reforms and wars.